PKM STRENGTHENING ECO-TOURISM THROUGH TOURISM BRENDING TOWARDS A CREATIVE VILLAGE IN TAMANSARI VILLAGE, LICIN DISTRICT, BANYUWANGI REGENCY - Eko Lisitiwikono (International Jurnal of Education Schoolars, 2022)
Community Partnership Program (PKM) entitled PKM to Strengthen Ecotourism Villages through Licinding at Taman Wisata Banyuwangi District What is often called a Tourism Village is a program that is socialized by the Ministry of Tourism and is followed up by the Tourism Office in the Province, City, and Regency. Through the concept of a creative village. Tamansari Village is a village that is part of the Banyuwangi Regency Tourism Office Program and in collaboration with LPPM PGRI Banyuwangi University, through the PKM Program. The PKM program is expected to focus more on improving the welfare of the economic community and knowledge in Tamansari Village. In realizing a creative village, Tamansari Village is a village that has experienced very rapid and strategic tourism development and is located in the Ijen natural tourism park area. Not only that, in Tamansari Village there are Sendang Seruni tours, terracotta gandrung parks, pine forest tours, flower villages and mining villages. . Tamansari Village community. Solutions to problems can be provided based on the results of problem identification that become a reference in preparation, implementation, monitoring, evaluation and reporting. The solutions that can be offered to partners are 1. Coffee brewing Barista training for partners and youth in Tamansari village, 2. business management and marketing training for the coffee business community in Tamansari village, 3. assistance in managing product permits at MUI and Balai POM 4. Appropriate technological tools in the form of a coffee crusher. To meet the quantity and quality of production, the expected achievement indicators from the implementation of community service in Tamansari Village, namely: increasing community knowledge and skills, increasing the number of coffee products produced, increasing the quality of coffee products, increasing the income of the people of Tamansari Village with the wider area of productpackaged coffee. So that Tamansari Village coffee is not only popular in the Licin District area, but Tamansari Village Coffee can also be one of the typical Banyuwangi coffee productions that must be sought after by local and foreign tourists